Selected abstracts from 10th STMS World Congress (Tokyo 2008), Part III - Maquirriain, J. (Medicine and Science in Tennis, 2009)
The Society for Tennis Medicine and Science held its 10th World Congress on the 3rd and 4th of October in Japan. Dr. Moroe Beppu was the program committee chairman of this landmark meeting as it was the first STMS congress in the Orient. The program included high quality posters and podium presentations. The JMST Editorial Staff has selected those original studies specific focused on Tennis Medicine and Science. In this part you find the following abstracts: - Field Test and Basic Strength for Tennis (Kazuhiro Suda, Kaoru Umebayashi), - Differences in Body Composition in Relation to Performance Level in Male Collegiate Tennis Players (Kouji Okumura, Suguru Torii); - The Effects of Self-talk on Anticipation Responses in Receiving Tennis Serves (Masanori Takahashi, Judy L. Van Raalte, Nobuaki Tanaka, Masayuki Sato, Jun Kamiwazumi, Fumio Mizuochi); - Investigation of the Psychological Aspects of Male Junior Tennis Players in Japan (Nobuaki Tanaka, Masanori Takahashi, Hiroko Uchijo, Daisuke Hirata, Morihiro Takeda, Kaoru Umebayashi, Masayuki Sato, Shuhei Sato); - Comparison of the Two Different Periodized Training Programs in Male College Tennis Players (Taira Imanishi, Kaoru Umebayashi, Keiko Matsubara); - Age Trends in Professional Tennis Players Career: Are Champions Really Precocious? (Javier Maquirriain); - Analysis of Injuries and Medical Check for All Japan Junior Tennis Championships in Japan (Ayumi Fujisawa, Shuzo Okudaira, Keisuke Ohta, Kaoru Umebayashi, Takahide Miyama, Yasukazu Yonetani, Moroe Beppu, Ken Nakata, Yukio Kawai, Yoko Yamasaki); - Full-thickness Rotator Cuff Tear in Middle-Aged Tennis Players (Teruhisa Mihata, Muneaki Abe, Chisato Watanabe, Mitsuo Kinoshita); Incidence and Injury Mechanism of ACL Injury in Tennis Player (Yasukazu Yonetani, Ken Nakata); - Foot Structure in Collegiate Tennis Players Shows Side-to-side Difference (Nobuyuki Shinozuka, Suguru Torii, Kouji Okumura).